Dynamic Geometry: P123

Geometry Level 5

The diagram shows a parabola y = k x 2 y=kx^2 , the positive real number k k is a parameter allowing us to shrink or widen the parabola freely. Inside are inscribed an infinite number of circles on top of each other. When the circumference of the 10 0 t h 100^{th} circle is equal to 199 π 25 \dfrac{199\pi }{25} , the sum of the reciproqual of the area of all circles converges to p π q \dfrac{p\pi }{q} , where p p and q q are coprime positive integers. Find p + q p+q . Note: the first circle is the largest we can inscribe.


The answer is 627.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Apr 28, 2021

Let the radius of the n n th circle be r n r_n . First find r 1 r_1 , the radius of the largest inscribed lowest circle. The lowest circle satisfies

{ x 2 + ( y r 1 ) 2 = r 1 2 y = k x 2 x 2 + ( k x 2 r 1 ) 2 = r 1 2 x 2 + k 2 x 4 2 k r 1 x 2 + r 1 2 = r 1 2 x 2 ( 1 + k 2 x 2 2 k r 1 ) = 0 x = { 0 ± 2 k r 1 1 k \begin{cases} x^2 + (y-r_1)^2 = r_1^2 \\ y = kx^2 \end{cases} \\ \begin{aligned} \implies x^2 + (kx^2 - r_1)^2 & = r_1^2 \\ x^2 + k^2x^4 - 2kr_1x^2 + r_1^2 & = r_1^2 \\ x^2(1 + k^2 x^2 - 2kr_1) & = 0 \\ \implies x & = \begin{cases} 0 \\ \pm \dfrac {\sqrt{2kr_1-1}}k \end{cases} \end{aligned}

When the circle is inscribable by the parabola, there is only one root x = 0 x=0 . This means that x = 2 k r 1 1 k x = \dfrac {\sqrt{2kr_1 -1}}k is 0 0 or imaginary. This means that 2 k r 1 1 0 r 1 1 2 k 2kr_1 - 1 \le 0 \implies r_1 \le \dfrac 1{2k} .

Now consider r n r_n . Let the lowest point of the n n th circle be ( 0 , h n 1 ) (0, h_{n-1}) and the point it is tangent to the right side of y = k x 2 y=kx^2 be P ( x , y ) P(x,y) . Then P ( x , y ) P(x,y) satisfies:

{ x 2 + ( y h n 1 r n ) 2 = r n 2 . . . ( 1 ) y = k x 2 . . . ( 2 ) \begin{cases} x^2 + (y-h_{n-1} - r_n)^2 = r_n^2 & ...(1) \\ y = kx^2 & ...(2) \end{cases}

At P ( x , y ) P(x,y) , the gradient of the circle is the same as that of the parabola, d y d x = 2 k x \dfrac {dy}{dx} = 2kx . Differentiating the equation of the circle w.r.t. x x :

2 x + 2 ( y h n 1 r n ) d y d x = 0 Note that d y d x = 2 k x 2 x + 2 ( y h n 1 r n ) ( 2 k x ) = 0 Since x 0 1 + 2 k ( y h n 1 r n ) = 0 y h n 1 r n = 1 2 k \begin{aligned} 2x + 2(y - h_{n-1} - r_n) \blue{\frac {dy}{dx}} & = 0 & \small \blue{\text{Note that }\frac {dy}{dx} = 2kx} \\ 2x + 2(y - h_{n-1} - r_n)(2kx) & = 0 & \small \blue{\text{Since }x \ne 0} \\ 1 + 2k(y - h_{n-1} - r_n) & = 0 \\ \implies y - h_{n-1} - r_n & = - \frac 1{2k} \end{aligned}

Then the equation of circle ( 1 ) (1) becomes:

x 2 + ( 1 2 k ) 2 = r n 2 Since y = k x 2 and y = h n 1 + r n 1 2 k h n 1 + r n k 1 2 k 2 + 1 4 k 2 = r n 2 r n 2 r n k + 1 4 k 2 = h n 1 k ( r n 1 2 k ) 2 = h n 1 k r n = h n 1 k + 1 2 k \begin{aligned} x^2 + \left(-\frac 1{2k}\right)^2 & = r_n^2 & \small \blue{\text{Since }y=kx^2 \text{ and }y = h_{n-1}+r_n-\frac 1{2k}} \\ \frac {h_{n-1}+r_n}k - \frac 1{2k^2} + \frac 1{4k^2} & = r_n^2 \\ r_n^2 - \frac {r_n}k + \frac 1{4k^2} & = \frac {h_{n-1}}k \\ \left(r_n - \frac 1{2k} \right)^2 & = \frac {h_{n-1}}k \\ \implies r_n & = \sqrt{\frac {h_{n-1}}k} + \frac 1{2k} \end{aligned}

We can prove by induction that r n = 2 n 1 2 k r_n = \dfrac {2n-1}{2k} . When n = 1 n=1 , y 0 = 0 y_0 = 0 , r 1 = 1 2 k \implies r_1 = \dfrac 1{2k} . The claim is true for n = 1 n=1 . Assuming the claim is true for n n , then

r n + 1 = y n k + 1 2 k = h n 1 + 2 r n k + 1 2 k = ( r n 1 2 k ) 2 + 2 r n k + 1 2 k = r n + 1 2 k + 1 2 k = 2 n 1 2 k + 1 2 k + 1 2 k = 2 ( n + 1 ) 1 2 k \begin{aligned} r_{n+1} & = \sqrt{\frac {y_n}k} + \frac 1{2k} = \sqrt{\frac {h_{n-1}+2r_n}k} + \frac 1{2k} = \sqrt{\left(r_n - \frac 1{2k} \right)^2 + \frac {2r_n}k} + \frac 1{2k} \\ & = r_n + \frac 1{2k} + \frac 1{2k} = \frac {2n-1}{2k} + \frac 1{2k} + \frac 1{2k} = \frac {2(n+1)-1}{2k} \end{aligned}

The claim is also true for n + 1 n+1 , hence it is true for all n 1 n \ge 1 .

When the circumference of the 100 100 th circle,

2 π r 100 = 199 π 25 2 2 ( 100 ) 1 2 k = 199 25 k = 25 \begin{aligned} 2\pi r_{100} & = \frac {199 \pi}{25} \\ 2 \cdot \frac {2(100)-1}{2k} & = \frac {199}{25} \\ \implies k & = 25 \end{aligned}

The sum of all reciprocals of area of circle,

n = 1 1 π r n 2 = n = 1 2500 ( 2 n 1 ) 2 π = 2500 π 3 4 ζ ( 2 ) = 2500 π 3 4 π 2 6 = 625 π 2 \begin{aligned} \sum_{n=1}^\infty \frac 1{\pi r_n^2} & = \sum_{n=1}^\infty \frac {2500}{(2n-1)^2\pi} = \frac {2500}\pi \cdot \frac 34 \zeta(2) = \frac {2500}\pi \cdot \frac 34 \cdot \frac {\pi^2}6 = \frac {625\pi}2 \end{aligned}

Therefore p + q = 625 + 2 = 627 p+q = 625+2 = \boxed{627} .


Notation: ζ ( ) \zeta (\cdot) denotes the Riemann zeta function .

Valentin Duringer
Apr 28, 2021
  • Let us evaluate the radus of the first circle in terms of k k , this circle needs to be the largest possible.
  • We can write its equation : x 2 + ( y r 1 ) 2 r 1 2 = 0 x^2+\left(y-r_1\right)^2-r_1^2=0
  • We can combine the two equations: { x 2 + ( y r 1 ) 2 r 1 2 = 0 y = k x 2 \begin{cases}x^2+\left(y-r_1\right)^2-r_1^2=0\\y=k\cdot x^2\end{cases}
  • We get x ² + ( k x ² r 1 ) 2 r 1 2 = 0 x²+\left(k\cdot \:x²-r_1\right)^2-r_1^2=0 < = > <=> x 4 k 2 + x 2 ( 1 2 k r 1 ) = 0 x^4\cdot k^2+x^2\left(1-2kr_1\right)=0
  • We evaluate Δ x = ( 1 2 k r 1 ) 2 \Delta \:_x=\left(1-2kr_1\right)^2 and set it equal to 0 0 : ( 1 2 k r 1 ) 2 = 0 < = > r 1 = 1 2 k \left(1-2kr_1\right)^2=0\:<=>r_1=\dfrac{1}{2k}
  • We can use a similar method to get the next radii:
  • r 1 = 1 2 k r_1=\dfrac{1}{2k} ; r 2 = 3 2 k r_2=\dfrac{3}{2k} ; r 3 = 5 2 k r_3=\dfrac{5}{2k} ; r 4 = 7 2 k r_4=\dfrac{7}{2k} ; r 5 = 9 2 k r_5=\dfrac{9}{2k}

  • This allows us to identify a pattern, r n = 2 n 1 2 k r_n=\dfrac{2n-1}{2k}\:\:

  • Then P 100 = 2 100 1 2 k 2 π = 199 π 25 P_{100}=\dfrac{2\cdot 100-1}{2k}\cdot 2\pi =\dfrac{199\pi }{25} < = > <=> k = 25 k=25
  • Now we can find n = 1 ( 2 25 2 n 1 ) 2 1 π \sum _{n=1}^{\infty }\:\left(\dfrac{2\cdot \:25}{2n-1}\right)^2\cdot \dfrac{1}{\pi } and we get 625 π 2 \dfrac{625\pi }{2}
  • Finally 625 + 2 = 627 625+2=627

For circle, it should be circumference instead of perimeter. It should be reciprocal instead of inverse.

Chew-Seong Cheong - 1 month, 2 weeks ago

Log in to reply

OK i ll correct when i can.

Valentin Duringer - 1 month, 2 weeks ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...